Atmospheric variability at the summit of Sierra Negra, Mexico, from 2012 July to 2015 October. Issue 3 (22nd September 2017) - Barrantes, M.; Valdés-Galicia, J. F.; González, L. X.; Carrasco, E.; Carramiñana, A.; Reyes, J.; Musalém, O.; Hurtado, A.
Abstract: Sierra Negra (SN) is a high summit (4580 m asl) inside the Pico de Orizaba National Park in eastern Mexico (coordinates 18.98N, 97.46W). Its location is favourable for astrophysical observations, therefore it has been selected as the site of various observatories. In this work, the behaviour of several atmospheric parameters (pressure, temperature, wind speed and relative humidity) was performed for the period 2012 July to 2015 October. The parameters chosen are known to have some influence in the time variability of the cosmic ray flux from the top of the atmosphere to the observation place. This study will help a proper characterization of the atmosphere. Moreover, a comparison with a similar study done a decade ago by Carrasco et al. allows us to analyse the evolution of the parameters with time and assess the stability of the atmospheric conditions of the site. Similarities and differences with the Carrasco et al. study are discussed.